Treatment of acute severe ulcerative colitis using accelerated infliximab regimen based on infliximab trough level: A case report - Sousa de Vasconcelos Garate, Ana Lorena [UNESP] (2021)
BACKGROUND Acute severe ulcerative colitis (ASUC) is a complication of ulcerative colitis associated with high levels of circulating tumor necrosis factor alpha, due to the intense inflammation and faster stool clearance of anti-tumor necrosis factor drugs. Dose-intensified infliximab treatment can be beneficial and is associated with lower rates of colectomy. The aim of the study was to present a case of a patient with ASUC and megacolon, treated with hydrocortisone and accelerated scheme of infliximab that was monitored by drug trough level. CASE SUMMARY A 22-year-old female patient diagnosed with ulcerative colitis, presented with diarrhea, rectal bleeding, abdominal pain, vomiting, and distended abdomen. During investigation, a positive toxin for Clostridium difficile and colonic dilatation of 7 cm consistent with megacolon were observed. She was treated with oral vancomycin for pseudomembranous colitis and intravenous hydrocortisone for severe colitis, which led to the resolution of megacolon. Due to the persistent severe colitis symptoms, infliximab 5 mg/kg was prescribed, monitored by drug trough level (8.8 mu g/mL) and fecal calprotectin of 921 mu g/g (< 30 mu g/g). Based on the low infliximab trough level after one week from the first infliximab dose, the patient received a second infusion at week 1, consistent with the accelerated regimen (infusions at weeks 0, 1, 2 and 6). We achieved a positive clinical and endoscopic response after 6 mo of therapy, without the need for a colectomy. CONCLUSION Infliximab accelerated infusions can be beneficial in ASUC unresponsive to the treatment with intravenous corticosteroids. Longitudinal studies are necessary to define the best therapeutic drug monitoring and treatment regimen for these patients.